2007
DOI: 10.1074/jbc.m703789200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Functional Analyses of the Type II Acyl Carrier Proteins of Fatty Acid Biosynthesis

Abstract: Acyl carrier protein (ACP) is a key component of the fatty acid synthesis pathways of both type I and type II synthesis systems. A large number of structure-function studies of various type II ACPs have been reported, but all are in vitro studies that assayed function or interaction of mutant ACPs with various enzymes of fatty acid synthesis or transfer. Hence in these studies functional properties of various mutant ACPs were assayed with only a subset of the many ACP-interacting proteins, which may not give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 61 publications
4
58
1
Order By: Relevance
“…The lack of function of the L. lactis and E. faecalis AcpAs could be explained by the failure of these two highly similar ACPs to be modified by the E. coli AcpS 4Ј-phosphopantetheinyl transferase. However, upon co-expression with the promiscuous B. subtilis Sfp 4Ј-phosphopantetheinyl transferase, both AcpA proteins were modified but remained unable to restore growth to a conditionally lethal acpP mutant strain of E. coli (4). These findings were puzzling because we had previously observed that genes from both of these closely related bacteria could replace the functions of E. coli fatty acid genes in vivo (6 -8).…”
contrasting
confidence: 40%
See 1 more Smart Citation
“…The lack of function of the L. lactis and E. faecalis AcpAs could be explained by the failure of these two highly similar ACPs to be modified by the E. coli AcpS 4Ј-phosphopantetheinyl transferase. However, upon co-expression with the promiscuous B. subtilis Sfp 4Ј-phosphopantetheinyl transferase, both AcpA proteins were modified but remained unable to restore growth to a conditionally lethal acpP mutant strain of E. coli (4). These findings were puzzling because we had previously observed that genes from both of these closely related bacteria could replace the functions of E. coli fatty acid genes in vivo (6 -8).…”
contrasting
confidence: 40%
“…Escherichia coli ACP, the most thoroughly studied member of this protein family, is a small (77 residues; molecular weight, 8,860), very acidic (pI of 4.1), and extremely soluble protein. In prior work, we reported that ACP species encoded by 11 diverse bacteria plus that of the apicoplast of the malarial protozoan parasite Plasmodium falciparum functionally replaced E. coli ACP in vivo (4). This generality was unforeseen because E. coli ACP interacts with 21 different lipid metabolism enzymes (5), virtually all of which are essential for growth.…”
mentioning
confidence: 99%
“…7A). Consistent with the finding that V. harveyi wild-type ACP is able to complement growth of an E. coli strain with a temperature-sensitive ACP (NRD224) at the restrictive temperature (35), expression of the linL46W protein led to strong complementation of the CY1861 strain in the presence of glucose and IPTG. Strikingly, expression of the cycL46W protein under similar conditions also led to complementation (Fig.…”
Section: Resultssupporting
confidence: 71%
“…3). It was shown previously that the acp Bsu gene compensated for the acpP(Ts) mutation in E. coli (6). This demonstrated again that fusion with the two-hybrid domain did not alter the function of the protein.…”
Section: Resultsmentioning
confidence: 51%